Deep Learning Framework for Arabic Course in Higher Education - Albantani, Azkia Muharom; Ardiansyah, Ade Arip; Zubaidah; Sahrir, Muhammad Sabri (Institut Agama Islam Negeri Palangka Raya, 2025)
This study explores the application of Deep Learning frameworks in Arabic language courses in higher education, focusing on four key dimensions: pedagogical practices, learning partnerships, learning environments, and digital utilization. Each framework serves as a critical pillar in addressing challenges and enhancing the effectiveness of Arabic language teaching, which is characterized by its linguistic and cultural complexities. The study highlights the need for innovative pedagogical approaches emphasizing conceptual understanding and practical application, collaborative partnerships among students, faculty, and communities, and supportive and inclusive learning environments. Moreover, integrating digital tools and resources is presented as a transformative strategy to create interactive and adaptive learning experiences. By examining these four frameworks, this article provides insights into designing a holistic, student-centered, and technologically enhanced learning process for Arabic language education. The findings underscore the importance of integrating these frameworks to produce graduates with comprehensive linguistic proficiency and critical thinking skills capable of engaging in global and multicultural contexts.